Targeted temperature management after cardiac arrest: Updated meta-analysis of all-cause mortality and neurological outcomes. (September 2019) - Abdalla, Mohammed; Mohamed, Abdelnasir; Mohamed, Wiam; Khtab, Khlwd; Cattoni, Hugo; Salih, Mohammed
Abstract: Background: Cardiac arrest carries high mortality and morbidity burden. Different studies showed conflicting data regarding outcomes of targeted temperature management (TTM) for cardiac arrest. The purpose of this meta-analysis is to systematically determine the effect of TTM on all-cause mortality and neurological outcomes after cardiac arrest. Methods: We conducted a systematic search for randomized controlled trials in Pubmed, Cochrane & ScienceDirect. Primary outcomes were neurological outcome and all-cause mortality. Results: Nine randomized controlled trials utilizing data for in-hospital and out-of-hospital cardiac arrest were selected for meta-analysis. Total number of patients included was 1592. Mortality was lower in targeted temperature management group (OR 0.637, 95% CI 0.436–0.93, p-value 0.019, I 2 = 44.78%, n = 1592). Therapeutic hypothermia group also demonstrated reduction in poor neurological outcomes (OR 0.582, 95% CI 0.363–931, p-value 0.024, I 2 = 56.79%, n = 1567). Subgroup analysis was conducted, after excluding in-hospital cardiac arrest patients, and demonstrated reduction in poor neurological outcome (OR 0.562, 95% CI 0.331–0.955, p-value 0.033, I 2 = 61.78%, n = 1480) and mortality in out-of-hospital cardiac arrest patients (OR 0.674, 95% CI 0.454–999, p-value 0.049, I 2 = 43.8%, n = 1505). Conclusion: Targeted temperature management after cardiac arrest may be associated with improvement in all-cause mortality and reduction in poor neurological outcome.